Substantive components of personal functioning of military servants according to the level of education - Mushkevych, Valentyn (Psychological Prospects Journal, 2022)
Purpose was to test the hypothesis of significant differences in the level of severity of frustration, aggression and psycho-emotional burnout in subjects of different educational levels.Methods. To study the quality of the characteristics of the subjects, relevant to the content indicators of their frustration, aggression and psycho-emotional burnout, we used the method of diagnosing the level of social frustration designed by L. Wasserman, the method of studying frustrational reactions by S. Rosenzweig, the method of diagnosing self-assessment of mental states by G. Eisenko. A. Bassa-A. Darki, the method of studying the aggression by E. Wagner, the method of diagnosing the level of emotional burnout by V. Boyko.Results. It was found that a significantly higher degree of dissatisfaction with the field of medical care, the opportunity to spend vacations, dissatisfaction with living conditions, the presence of "communication" in aggression are observed in those surveyed servicemen who have higher education. Significantly higher degree of dissatisfaction with their position in society, dissatisfaction with their own way of life in general, the presence of a type of behavior in frustration "extrapunitive reaction with fixation on self-defense", suspicion, hostility, severity of emotional burnout "emotional alienation" and emotional symptoms of psycho-vegetative disorders "are demonstrated by subjects with secondary education. According to our observations the highest degree of dissatisfaction with the level of their own education, dissatisfaction with the relationship with spouses, negativism, emotional burnout syndrome of feeling "driven into a corner", a symptom of emotional burnout "dissatisfaction with yourself" are shown by respondents with incomplete higher education. Significantly higher degree of dissatisfaction with the way of spending their leisure time, higher degree of manifestation of directiveness is characterized by the type of frustration reaction "impulsive reaction with fixation on self-defense", "extrapunitive reaction with fixation on satisfaction of needs", "fear" of aggression, "description" of aggression, manifestation of feeling offended, an indicator of "guilt", a symptom of emotional burnout "emotional deficit", a symptom of emotional burnout "general level of psycho-emotional burnout", a symptom of emotional burnout, such as "emotional and moral disorientation" have been observed in those subjects who have incomplete secondary education. Subjects with secondary special education demonstrate a significantly higher indicator of the type of frustrating behavior "impulsive reaction with fixation on the satisfaction of needs", a symptom of emotional burnout "experiencing psycho-traumatic circumstances".Conclusions. It was stated that in general the educational level of the subjects is not related to the manifestation of anxiety, frustration, aggression and rigidity.